Pendidikan Politik Bung Karno Untuk Taruna Merah Putih Nganjuk Sebagai Penggerak Pemilih Pemula Dalam Pemilu 2024 - Nara Setya Wiratama; Zainal Afandi; Agus Budianto; Rindi Anggraini; Ari Widya Utomo (Pakis Journal Institute, 2024)
Political education really needs to be transmitted to members of youth organizations so that they have good political skills. Bung Karno was a proclaimer, explorer of Pancasila and the first president of Indonesia who had visionary political views. The Community Service Team of the History Education Study Program, Universitas Nusantara PGRI Kediri would like to provide Bung Karno's Political Education for the Taruna Merah Putih Nganjuk as a Motivator of New Voters in the 2024 General Election. This service aims to: (1) Increase political understanding of the Taruna Merah Putih Nganjuk youth organization, and (2) Increasing insight into Bung Karno's thinking in the Indonesian Centric political movement. The methods used in service activities are lecture and demonstration methods. The lecture method is to convey the principles of Political Education, Bung Karno's thoughts, and current political conditions and ideal politics, while the demonstration method is to provide participants with the opportunity to practice speaking to put into practice the political knowledge that has been gained through discussion and question and answer. Based on the mentoring activities carried out, out of 30 participants, the results were that 27 participants were very satisfied with this activity and were able to complete the task well. The other 3 participants had technical problems. So it can be concluded that this service activity was successful.